Republic of Latvia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper analyses the implications of global value chains (GVC) participation for Latvia's competitiveness and exposure to risks. Using a structural model, it assesses Latvia's competitiveness through different real effective exchange rate (REER) measures and examines the main factors behind differences in the measures. Based on this analysis, the paper suggests policy options to strengthen Latvia's competitiveness. The paper also estimates the impact of an appreciation of the GVC related REER measure on value added export growth and real GDP growth, and finds sizable effects, suggesting that a rapid labor market tightening could lead to erosion in competitiveness and reduction in growth. Finally, trade tension induced tariff hikes may have significant cost for Latvia, especially in terms of value added produced in the country. Trade tension induced tariff hikes are likely to have moderate costs for Latvia in terms of value added produced in the country. In this regard, policies aimed at enhancing product sophistication or quality and export market diversification could mitigate Latvia's exposure to trade shocks in GVCs.